Steady state and time-resolved fluorescence studies of a hemagglutinin from Moringa oleifera - Katre, Uma V.; Suresh, C. G.; Khan, Mohammad Islam; Gaikwad, Sushama M. (Journal of Fluorescence, 2008)
The saccharide binding and conformational characterization of a hemagglutinin, a low molecular weight protein from the seeds of Moringa oleifera was studied using steady state and time resolved fluorescence. The lectin binds sugars LacNAc (K-a = 1380 M-1) and fructose (K-a = 975 M-1), as determined by the fluorescence spectroscopy. It has a single tryptophan per monomer which is exposed on the surface and is in a strong electropositive environment as revealed by quenching with iodide. Quenching of the fluorescence by acrylamide involved both static (K-s = 0.216 M-1) and collisional (K-sv= 8.19 M-1) components. The native protein showed two different lifetimes, tau(1) (1.6 ns) and tau(2) (4.36 ns) which decrease and get converted into a single one, (2.21 ns) after quenching with 0.15 M acrylamide. The bimolecular quenching constant, k(q) was 7.55 x 10(11) M-1 s(-1). ANS binding studies showed that the native protein has exposed hydrophobic patches which get further exposed at extreme acidic or alkaline pH. However, they get buried in the interior of the protein in presence of 1 M GdnHCl or urea.
Keywords: ANS binding; fluorescence; Hemagglutinin; lifetime; Moringa oleifera; saccharide binding; Solute quenching

Conformational and functional transitions in class II alpha-mannosidase from aspergillus fischeri - Shashidhara, K. S.; Gaikwad, Sushama M. (Journal of Fluorescence, 2010)
The conformational transitions in an oligomeric and high molecular weight class II alpha-mannosidase from Aspergillus fischeri were examined using fluorescence and CD spectroscopy under chemical, thermal and acid denaturing conditions. The enzyme lost the activity first and then the overall folded conformation and secondary structure. The midpoint values of GdnHCl mediated changes measured by inactivation; fluorescence and negative ellipticity were 0.48 M, 1.5 M and 1.9 M, respectively. The protein almost completely unfolded in 4.0 M GdnHCl but not at 90 A degrees C. The inactivation and unfolding were irreversible. At pH 2.0, the protein exhibited molten-globule like intermediate with rearranged secondary and tertiary structures and exposed hydrophobic amino acids on the surface. This species showed increased accessibility of Trp to the quenchers and got denatured with GdnHCl in a different manner. The insoluble aggregates of a thermally denatured protein could be detected only in the presence of 0.25-0.75 M GdnHCl.
Keywords: Aggregation; alpha-Mannosidase; ANS binding; Circular dichroism; fluorescence; GdnHCl; Hydrobicity; Thermal denaturation